2022
DOI: 10.4491/eer.2022.037
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different machine learning algorithms to estimate liquid level for bioreactor management

Abstract: Estimating the liquid level in an anaerobic digester can be disturbed by its closedness, bubbles and scum formation, and the inhomogeneity of the digestate. In our previous study, a soft-sensor approach using seven pressure meters has been proposed as an alternative for real-time liquid level estimation. Here, machine learning techniques were used to improve the estimation accuracy and optimize the number of sensors required in this approach. Four algorithms, multiple linear regression (MLR), artificial neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Subsequent to this, a simple linear regression analysis was conducted based on the centroid values derived from the K-mean clustering process. Linear regression is the most common approach for modeling numeric data and can be adapted to almost all types of data [41].…”
Section: Unsupervised and Supervised Learning In Machine Learningmentioning
confidence: 99%
“…Subsequent to this, a simple linear regression analysis was conducted based on the centroid values derived from the K-mean clustering process. Linear regression is the most common approach for modeling numeric data and can be adapted to almost all types of data [41].…”
Section: Unsupervised and Supervised Learning In Machine Learningmentioning
confidence: 99%
“…Limited use in the presence of large datasets, questionable model interpretability and lack of uncertainty disclosure associated with prediction hamper further dissemination. Has been gradually replaced in several settings by other methods, e.g., artificial neural networks and random forests, as these also provide more accurate predictions [2,[118][119][120].…”
Section: Support Vector Machines (Svms)mentioning
confidence: 99%
“…The tests concluded that random forest was the best algorithm producing more consistent results with low error rate and more than 90% accuracy in the prediction of n-caproate and n-caprylate ( Liu et al., 2022a ). To predict the accuracy of real-time liquid level four ML algorithms, multiple linear regression (MLR), artificial neural network (ANN), random forest (RF), and support vector machine (SVM) with radial basis kernel were analyzed and found that ANN and RF models performed well ( Yu et al., 2022 ).…”
Section: Ai-based ML Algorithms In Recombinant Protein Productionmentioning
confidence: 99%